Baryon-induced collapse of dark matter cores into supermassive black holes - Argüelles, Carlos Raúl (2024)
Nonlinear structure formation for fermionic dark matter particles leads to dark matter density profiles with a degenerate compact core surrounded by a diluted halo. For a given fermion mass, the core has a critical mass that collapses into a supermassive black hole (SMBH). Galactic dynamics constraints suggest a ∼100 keV/c² fermion, which leads to ∼10⁷M⊙ critical core mass. Here, we show that baryonic (ordinary) matter accretion drives an initially stable dark matter core to SMBH formation and determines the accreted mass threshold that induces it. Baryonic gas density ρb and velocity vb inferred from cosmological hydrosimulations and observations produce sub-Eddington accretion rates triggering the baryon-induced collapse in less than 1 Gyr. This process produces active galactic nuclei in galaxy mergers and the high-redshift Universe. For TXS 2116–077, merging with a nearby galaxy, the observed 3 × 10⁷M⊙ SMBH, for Qb = pb/vb³= 0.125M⊙ /(100 km s pc)³ , forms in ≈0.6 Gyr, consistent with the 0.5–2 Gyr merger timescale and younger jet. For the farthest central SMBH detected by the Chandra X-ray satellite in the z = 10.3 UHZ1 galaxy observed by the James Webb Space Telescope (JWST), the mechanism leads to a 4 × 10⁷M⊙ SMBH in 87–187 Myr, starting the accretion at z = 12–15. The baryon-induced collapse can also explain the ≈10⁷–10⁸M⊙ SMBHs revealed by JWST at z ≈ 4–6. After its formation, the SMBH can grow to a few 10⁹Me in timescales shorter than 1 Gyr via sub-Eddington baryonic mass accretion.